PELATIHAN KEWIRAUSAHAAN DALAM PEMBUATAN ANEKA MAKANAN BERBASIS EKONOMI KREATIF DI PESANTREN SIROJUL HUDA - Tati Handayani; Anggi Angga Resti; Anita Nopiyanti (LPPM Universitas Bina Bangsa, 2023)
Islamic boarding schools as educational institutions that provide religious and academic knowledge and apply them in everyday life. Islamic boarding schools cannot continue to depend on other parties, so there is a need for other alternatives to run the business that must be managed. By utilizing aloe vera which is easy to find and has many benefits, it is then processed into products with selling points, such as packaged drinks, soap, candy, and others. Aloe vera plants are easy to grow and live in cool areas like Bogor according to the location of partner Islamic boarding schools. The main problem is the skills needed by the students to process the aloe vera plant so that the results can be utilized within the Islamic boarding school environment. Therefore, the main objective of this community service activity is to hold aloe vera processing training to encourage the entrepreneurial spirit and skills of the students. This activity is a real contribution in empowering and empowering the students. From the results of the test given in the form of a questionnaire, more than 50% of respondents said they really understood the understanding of the material. And also on the benefits of the activity, as many as 75% said it was very useful. The results of this community service greatly contributed to increasing understanding and training regarding the aloe vera plant